Impact of Chinese ADRs: case study of MAPPAC method analysing China dual listing companies in the US equity market. (15th June 2021) - Guo, Haochen
China concepts stock is the stock in a company that operates in mainland China, and incorporated overseas, giving Chinese businesses access to foreign investment. In the US equity market, investors may have seen China concepts stock listed on the NYSE, NASDAQ, NYSE MKT take the form of American Depositary Receipt (ADR) instead of common stock. The motivation of this paper case by historically Chinese stock exchanges have been closed to foreign investment, which has driven businesses to form China concepts stock. As the country develops its capital markets, China's concepts stocks are expected to be a key driver to China's economic growth. This paper contributes to present the Chinese ADR has higher value investment scarcity and help new economic companies obtain reasonable valuations on the US equity market with more mature, investors are more rational and more suitable for long-term investment and value investment.